2001
DOI: 10.1007/pl00013737
|View full text |Cite
|
Sign up to set email alerts
|

Impact of global warming on the interannual and interdecadal climate modes in a coupled GCM

Abstract: In this study, we investigated the impact of global warming on the variabilities of large-scale interannual and interdecadal climate modes and teleconnection patterns with two long-term integrations of the coupled general circulation model of ECHAM4/OPYC3 at the Max-Planck-Institute for Meteorology, Hamburg. One is the control (CTRL) run with ®xed present-day concentrations of greenhouse gases. The other experiment is a simulation of transient greenhouse warming, named GHG run. In the GHG run the averaged geop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 31 publications
4
10
0
Order By: Relevance
“…However, observational studies have shown that the winter NAO can be characterized as having a weakly red spectrum with some long-range dependence (Stephenson et al, 2000;Stephenson and Pavan, 2003). Figures 3 and 4 also show no significant differences of NAO behavior between the first and second halves of the model integration, which is consistent with previous results (Ulbrich and Christoph, 1999;Hu et al, 2001). Disagreement between Figs.…”
Section: Nao-like Change In the Global Warming Scenariosupporting
confidence: 89%
See 3 more Smart Citations
“…However, observational studies have shown that the winter NAO can be characterized as having a weakly red spectrum with some long-range dependence (Stephenson et al, 2000;Stephenson and Pavan, 2003). Figures 3 and 4 also show no significant differences of NAO behavior between the first and second halves of the model integration, which is consistent with previous results (Ulbrich and Christoph, 1999;Hu et al, 2001). Disagreement between Figs.…”
Section: Nao-like Change In the Global Warming Scenariosupporting
confidence: 89%
“…Ulbrich and Christoph (1999) found that the disagreement between the NAO index change and the storm track intensification results from the northeastward shift of the northern center of action of the NAO. By examining the same scenario run, Hu et al (2001) also found that there is no significant change of the NAO index. Zorita and González-Rouco (2000) demonstrated the disagreement of the simulated long-term trends of the AO intensity between the HadCM2 and ECHAM4/OPYC CGCMs, although the simulated winter temperature increases averaged over the NH in the two models are very similar.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Attempts to address this question using climate models have again shown conflicting results, varying from slight decreases or little change in amplitude (Tett 1995;Knutson et al, 1997;Noda et al, 1999b;Collins, 2000b;Washington et al, 2001;Figure 9.26b) to a small increase in amplitude (Timmermann et al, 1999;Collins, 2000a; Figure 9.26a), which has been attributed to an increase in the intensity of the thermocline in the tropical Pacific. Knutson et al (1997) and Hu et al (2001) find that the largest changes in the amplitude of ENSO occur on decadal time-scales with increased multi-decadal modulation of the ENSO amplitude. Several authors have also found changes in other statistics of variability related to ENSO.…”
Section: Interannual Variability Ensomentioning
confidence: 99%